Table for two : fictions - Towles, Amor ([New York] : Viking, 2024)
"Six stories set in New York City and a novella in Los Angeles. The New York stories, most of which are set around the year 2000, take up everything from the death-defying acrobatics of the male ego, to the fateful consequences of brief encounters, and the delicate mechanics of compromise which operate at the heart of modern marriages. Throughout the stories, two characters often find themselves sitting across a table for two where the direction of their futures may hinge upon what they say to each other next. "-- Provided by publisher.
The line -- The ballad of Timothy Touchett -- Hasta Luego -- I will survive -- The bootlegger -- The DiDomenico fragment -- Eve in Hollywood.
Keywords: Fate and fatalism -- Fiction; New York (N.Y.) -- Fiction; Los Angeles (Calif.) -- Fiction; Bildungsromans; Short stories; Novellas